A Genome-Wide Association Study of Sprint Performance in Elite Youth Football Players. Issue 9 (September 2019) - Pickering, Craig; Suraci, Bruce; Semenova, Ekaterina A.; Boulygina, Eugenia A.; Kostryukova, Elena S.; Kulemin, Nickolay A.; Borisov, Oleg V.; Khabibova, Sofya A.; Larin, Andrey K.; Pavlenko, Alexander V.; Lyubaeva, Ekaterina V.; Popov, Daniil V.; et al.
Abstract : Abstract: Pickering, C, Suraci, B, Semenova, EA, Boulygina, EA, Kostryukova, ES, Kulemin, NA, Borisov, OV, Khabibova, SA, Larin, AK, Pavlenko, AV, Lyubaeva, EV, Popov, DV, Lysenko, EA, Vepkhvadze, TF, Lednev, EM, Leońska-Duniec, A, Pająk, B, Chycki, J, Moska, W, Lulińska-Kuklik, E, Dornowski, M, Maszczyk, A, Bradley, B, Kana-ah, A, Cięszczyk, P, Generozov, EV, and Ahmetov, II. A genome-wide association study of sprint performance in elite youth football players. J Strength Cond Res 33(9): 2344–2351, 2019—Sprint speed is an important component of football performance, with teams often placing a high value on sprint and acceleration ability. The aim of this study was to undertake the first genome-wide association study to identify genetic variants associated with sprint test performance in elite youth football players and to further validate the obtained results in additional studies. Using micro-array data (600 K–1.14 M single nucleotide polymorphisms [SNPs]) of 1, 206 subjects, we identified 12 SNPs with suggestive significance after passing replication criteria. The polymorphism rs55743914 located in the PTPRK gene was found as the most significant for 5-m sprint test ( p = 7.7 × 10 −7 ). Seven of the discovered SNPs were also associated with sprint test performance in a cohort of 126 Polish women, and 4 were associated with power athlete status in a cohort of 399 elite Russian athletes. Six SNPs were associated with muscle fiber type in a cohort of 96 Russian subjects. We also examined genotype distributions and possible associations for 16 SNPs previously linked with sprint performance. Four SNPs ( AGT rs699, HSD17B14 rs7247312, IGF2 rs680, and IL6 rs1800795) were associated with sprint test performance in this cohort. In addition, the G alleles of 2 SNPs in ADRB2 (rs1042713 & rs1042714) were significantly over-represented in these players compared with British and European controls. These results suggest that there is a genetic influence on sprint test performance in footballers, and identifies some of the genetic variants that help explain this influence.